2008
DOI: 10.1080/10428190802451254
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea, azacitidine and gemtuzumab ozogamicin therapy in patients with previously untreated non-M3 acute myeloid leukemia and high-risk myelodysplastic syndromes in the elderly: results from a pilot trial

Abstract: Elderly patients with acute myeloid leukemia (AML) and high-risk myelodysplastic syndromes (MDS) have a poor prognosis due to low response rates (26-46%) to standard chemotherapy and high treatment-related mortality (11-31%). In this Phase II study, we used a combination of hydroxyurea (HU), azacitidine and low dose gemtuzumab ozogamicin (GO) to assess its efficacy and toxicity in this group of patients. Twenty patients with non-M3 AML and MDS were treated with this regimen. The treatment was begun with HU 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…A randomized Phase III study of standard induction with or without GO in younger patients was terminated early for a lack of benefit and increased toxicity, leading to the FDA's request that it no longer be commercially available. However, GO could be beneficial in the elderly population in a variety of scenarios: as part of consolidation or maintenance therapy; with cytarabine (Piccaluga et al, 2004;Fianchi et al, 2008) or immunotherapy; with lower intensity therapies like azacitidine; (Nand et al, 2008) administered using a fractionated dosing regimen; (Taksin et al, 2007) or accompanying autologous transplantation (Cascavilla et al, 2008).…”
Section: Immunotherapymentioning
confidence: 99%
“…A randomized Phase III study of standard induction with or without GO in younger patients was terminated early for a lack of benefit and increased toxicity, leading to the FDA's request that it no longer be commercially available. However, GO could be beneficial in the elderly population in a variety of scenarios: as part of consolidation or maintenance therapy; with cytarabine (Piccaluga et al, 2004;Fianchi et al, 2008) or immunotherapy; with lower intensity therapies like azacitidine; (Nand et al, 2008) administered using a fractionated dosing regimen; (Taksin et al, 2007) or accompanying autologous transplantation (Cascavilla et al, 2008).…”
Section: Immunotherapymentioning
confidence: 99%
“…VOD, a severe complication with thrombosis of small liver veins, was reported with an incidence of 7-20% in studies using GO before chemotherapy [8,29,32,37]. However, in studies using GO after chemotherapy, incidence of VOD seems to be lower [22,33,36]. In our patient cohort, mainly including patients who received chemotherapy first followed by GO, no VOD was observed.…”
Section: Subsequent Treatmentmentioning
confidence: 48%
“…During myelosuppression, in almost all patients (88%) neutropenic fever emerged and four patients (17%) subsequently died due to infectious complications. Treatment-related mortality was reported to be 5-13% in published studies using GO after chemotherapy [22,33,36], whereas mortality in studies using GO before chemotherapy seemed to be higher (19-57%) [8,11,37,43]. Of note, multiple responses were observed in a single patient treated repeatedly with GO.…”
Section: Subsequent Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…6 Likewise, DNA methyltransferase I inhibitors such as azacitidine or decitabine have been demonstrated to enhance GO efficacy in vitro, 7,8 possibly through lowering of the apoptotic threshold, and early clinical studies have indicated activity in patients with AML. [9][10][11] These studies, together with the improved clinical activity reported when HDAC inhibitors are used with DNA methyltransferase I inhibitors, 12 prompted a phase I/II study with vorinostat and azacitidine as chemosensitizers for GO in the treatment of primary refractory AML or AML in first relapse (remission duration ≀12 months) requiring first salvage therapy. Epigenetic therapeutics such as the histone deacetylase inhibitor, vorinostat, and the DNA methyltransferase I inhibitor, azacitidine, enhance gemtuzumab ozogamicin efficacy in vitro.…”
Section: Introductionmentioning
confidence: 99%